Development and productization of microgreen tray for Plantui P6 - Kuusisto, Iiris (My University, 2020)
Modern indoor farming based on hydroponic cultivation creates new opportunities to answer growing demand of nutritious food in the world. Another rising field of food production is unmatured plants such as sprouts and microgreens, they also offer way to grow hyperlocal food which is a dense source of nutrition with small environmental impact. Together these two food trends can have significant impact to future of food security. This thesis aimed to create product that enables sprouts and microgreen cultivation in Plantui P6 hydroponic smart garden. Product was developed from early prototype to a working solution through iterative process and productization process was started. The main objective of the development was consumer driven design focusing on easy-to-use and rewarding experience. During project, a new method for microgreen growing was developed and productized, but sprouts growing method was left aside due to its incompatibility to P6 device hydroponic method. New microgreen tray product answers to current global trends as well as strengthens and creates new interest in the Plantui concept, therefore fulfilling the goals set out for this thesis.

Moderni vesiviljelyyn perustuva sisäviljely luo uuden tavan vastata terveellisten elintarvikkeiden kasvavaan kysyntään maailmassa. Toinen kasvava elintarviketuotannon ala on idut ja versot. Myös nämä nuoret kasvit tarjoavat tavan kasvattaa lähiruokaa, joka on ravinnerikasta ja ympäristöystävällistä. Yhdessä näillä ruokatrendeillä voi olla merkittävä vaikutus tulevaisuuden elintarviketuotantoon. Tämän opinnäytetyön tavoitteena oli luoda tuote, joka mahdollistaa itujen ja versojen viljelyn Plantui P6 -vesiviljelyälypuutarhassa. Tuote kehitettiin varhaisesta prototyypistä toimivaksi ratkaisuksi iteratiivisella prosessilla, jonka jälkeen aloitettiin tuotteistaminen. Kehityksessä päätavoitteena oli kuluttajalähtöinen suunnittelu, jossa keskityttiin saavuttamaan helppokäyttöinen ja palkitseva käyttäjäkokemus. Projektin aikana kehitettiin ja tuotteistettiin uusi menetelmä versojen viljelyyn, mutta itujen kasvatusmenetelmä jätettiin pois lopputuotteesta, koska se ei sopinut yhteen Plantui P6-laiteen toimintamenetelmän kanssa. Uusi Microgreen tray -tuote vastaa tämänhetkisiin globaaleihin trendeihin, sekä vahvistaa ja luo uutta kiinnostusta Plantui-konseptiin, täyttäen siten tämän tutkielman tavoitteet.
Keywords: hydroponics, indoor gardening, sprouts, microgreens, Plantui, functional food, product design